Peran Pola Asuh Orang Tua dalam Pembentukan Konsep Diri Siswa dan Prestasi Belajar di SMP Kecamatan Bantarkawung - Fuadah, Nurul; Kusrina, Tity; Paridjo, Paridjo (Universitas Nusantara PGRI Kediri, 2025)
This study aims to analyze the influence of parenting style and students' self-concept on academic achievement in Science, Mathematics, and English subjects at the junior high school level. This study uses a quantitative method, involving parents, students, and BK teachers in Bantarkawung District as samples. Data collection was carried out through questionnaires, and data analysis used descriptive statistics and multiple regression to determine the relationship between independent variables (parenting style and self-concept) with the dependent variable (academic achievement). The results showed that parenting style and self-concept had a significant effect on learning achievement. Parenting styles that support and encourage independence have been shown to help form positive self-concepts in students, which in turn have an impact on improving academic achievement. In addition, students with strong and positive self-concepts tend to show better learning outcomes. These findings indicate that appropriate parenting patterns and healthy self-concepts are important factors in supporting students' academic achievement.